Dinamika Konflik dan Jejak Perdagangan Senjata Di Tanah Papua - Latif, Syahrul Akmal; Shiddiqy, Muhammad Arsy Ash (Jayapangus Press, 2023)
This research describes the conflict dynamics and traces of the arms trade in Papua. Conflict and violence in Papua have become a kind of tangled thread and is a vertical conflict that has been going on for more than 50 years. The primary reason behind this conflict stems from the aspiration for an